Review of Economic Studies European Meetings: May 1989 (Review of Economic Studies, 1989)
Review of Economic Studies European Meetings: May 1989 Get access The Review of Economic Studies, Volume 56, Issue 4, October 1989, Page 643, https://doi.org/10.1093/restud/56.4.643 Published: 01 October 1989